Map of the distribution of diabetes mellitus cases and their treatment in the number of health workers and primary health care in Yogyakarta City District 2020 - Laferani, Yuni; Kusumadewi, Ni Nengah Sri (BKM Public Health and Community Medicine, 2024)
Purpose: One of the non-communicable diseases with the highest incidence rate at the global level is diabetes. The percentage of diabetes cases in Indonesia increased from 6.9% in 2013 to 10.9% in 2018. The Indonesian government, through the Ministry of Health, has made efforts to overcome diabetes due to the increasing incidence of diabetes. This study aims to describe the number of diabetes mellitus cases, the distribution map of health facilities, and various elements of the diabetes mellitus management program in Yogyakarta City in 2020. Methods: Descriptive analysis with quantitative approach using aggregate data at the sub-district level in Yogyakarta City. Data analysis using QGIS applications. Results: Distribution is shown by classifying the number of cases and the percentage of different diabetes cases in the sub-district, which is described by elements of diabetes management programs. Conclusion: The distribution of diabetes cases is based on the number of cases with the highest categories in the sub-districts of Umbulharjo, Gondokusuman, and Tegalrejo. Pakualaman sub-district has a very high percentage of diabetes cases coupled with intermediate accreditation status, the number of posbindu is 6-8, the number of nurses is less than 5, the number of health cases, and the number of medical laboratory technology is only one.